Development of high-efficiency oxy-fuel IGCC system - Yuso OKI (The Japan Society of Mechanical Engineers, 2016)
Carbon Capture and Storage (CCS) is regarded as a countermeasure for global warming, but introduction of conventional CCS system deteriorates thermal efficiency of power station. To find out its solution, a project has started by NEDO to develop the High-efficiency Oxy-fuel IGCC system, which can keep high efficiency even after capturing CO2. In this system, gasifying agent and combustion air is substituted by oxygen diluted by exhaust gas recirculated from gas turbine combustor. The target of this project was set as to achieve net thermal efficiency more than 42% at HHV basis, which is equivalent to state of the art coal-fired power station. Various approaches were done to confirm the concept of this system and to develop fundamental technologies necessary for the system since 2008 to 2014 under the support by NEDO. As good achievements were obtained till 2014, the project made another step for developing high efficiency oxy-fuel IGCC since 2015 as a 5 year joint project with MHI and MHPS under the support by NEDO. This paper introduces the latest status of this project executed by CRIEPI by referring several related papers.